Invasive pneumococcal pneumonia with massive empyema: a case report / Tin Nwe Latt and Noor Shafina Mohd Nor - Tin Nwe Latt; Mohd Nor, Noor Shafina (Faculty of Medicine, 2016)
Although the use of appropriate antibiotics has significantly improved the outcome of pneumonia, severe complications are still encountered. We report here of a case with invasive pneumococcal pneumonia with massive empyema. A 2-year-4-month old girl presented with fever for 8 days and intermittent cough for 2 weeks. On examination, reduced air entry with dullness on percussion was noted on the left lung. Chest ultrasound revealed moderate to gross pleural effusion with septations, for which left thoraco-centesis with insertion of pigtail tube was performed. Streptococcus pneumoniae was detected via polymerase chain reaction (PCR) test in the pleural fluid. Intravenous (IV) benzylpenicillin and ceftriaxone were given together with one course (5 days) of intrapleural urokinase to breakdown the septations. Timely and appropriate management of pneumonia including the use of thrombolytic agent is vital to ensure optimal outcome and reduce the need of invasive procedures in cases with massive empyema. Public awareness of pneumococcal vaccination is also essential as a part of preventive measures.